2021
DOI: 10.3390/su13095056
|View full text |Cite
|
Sign up to set email alerts
|

Representativeness in Geographical Indications: A Comparison between the State-Driven and Producer-Driven Systems in Vietnam and France

Abstract: This paper explores the issues of representativeness and participation in the collective processes involved in the elaboration of the geographical indications (GI) specifications and the governance of the GI initiatives. The objective is to understand the relationship among collective dynamics, representativeness of relevant stakeholders, and the legal frameworks for the protection of GIs. Using a qualitative methodology based on an analysis of six case studies in France and Vietnam, we show the role of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The authors found that the use of those techniques represents an interesting tool to enhance and protect the PDOs and PGIs of Italian products. Another study explored the representativeness of relevant stakeholders in the elaboration of GIs in France and Vietnam [12]. They recommended that the state needs to consult a wide range of stakeholders in the process of elaborating GIs, first the value-chain stakeholders, and second those outside the value chain, such as local authority representatives, traders, and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the use of those techniques represents an interesting tool to enhance and protect the PDOs and PGIs of Italian products. Another study explored the representativeness of relevant stakeholders in the elaboration of GIs in France and Vietnam [12]. They recommended that the state needs to consult a wide range of stakeholders in the process of elaborating GIs, first the value-chain stakeholders, and second those outside the value chain, such as local authority representatives, traders, and consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The complex interplay of diverse actors' resources, knowledge, interests, needs and worldviews is regulated by constitutional rules that apply to a particular place and time and determine who is involved in decision-making and who is excluded. Coordination among different actors is particularly important for the formulation of GI standards, the elaboration of which is based on knowledge, skills, practices, history, and culture of a community of people in a given geographical area (Allaire et al, 2011;Pick and Marie-Vivien, 2021). When experimenting with (new) food quality standards, such as those for GI, actors have access to certain knowledge, can anticipate and seek feedback on proposed modifications in food production and processing practices, and can learn from the experience of other producer organisations.…”
Section: Polycentric Governance and The Three Levels Of Rulesmentioning
confidence: 99%
“…As an antithesis to these international standards, GIslike the sui generis European Union (EU) GI regimeare based on a variety of decentralised defined regulatory frameworks that ensure a link between the product attributes and its place of origin and provide a space for local actors to discuss their own vision of the product (Pick and Marie-Vivien, 2021). In this article, we use France, Italy, and Austria as contrasting cases of GI governance to better understand how differences in governance structures affect the coordination of diverse interests and the adaptability of food quality standards to changing (local) contexts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations